ANALISA FORWARD KINEMATIC PADA SIMULATOR ARM ROBOT 5 DOF YANG MENGINTEGRASIKAN MIKROKONTROLER ARDUINO-UNO DAN LABVIEW - Munadi, Munadi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
An arm robot simulator has been developed, that capable in simulating a 5 degree of freedom robot manipulator, in which it was equipped with two-finger gripper mechanism at end-effector. This simulator is designed for educational purposes so that many students can easily understand when learning about robot manipulator. The simulator was developed using Ardiuno Uno with LabVIEW through the Firmata interface for controlling the actuators (servo motors). Ardiuno Uno was chosen because it can interact with LabVIEW that will be able to control the angular position of servo motor easily. Angular position errors that occur on the servo motor can be solved by using a numerical program functions and numerical multiply divided on LabVIEW. For analysis, this paper presents the forward kinematics problem which is concerned with the relationship between the individual joints of the arm robot simulator and the position and orientation of the tool or end-effector. The analysis result is carried out in MATLAB.